The Relativity between Sustainable Management and Turnaround Management - Katits Etelka (TÁRSADALOM – GAZDASÁG – TERMÉSZET: SZINERGIÁK A FENNTARTHATÓ FEJLŐDÉSBEN, 2023)
The business practice of recent years could not do without the application of change and turnaround management, as well as the incorporation of sustainability principles into the management of companies. The goal is to examine the implementation of the EU directive, according to which companies can create long-term, sustainable values instead of short-term benefits. We are examining the possibilities and driving forces for making this a reality in the Hungarian agricultural sector. Our research questions: Why and how can corporate sustainable management, growth and value creation build on each other in practice? What are the necessary corporate quantitative and qualitative frameworks in today’s uncertain world? Why and how are corporate turnaround management and sustainability related? Does sustainable reorganization management technique exist in the Hungarian agricultural sector at all? Based on the results obtained from comparative financial and economic analysis of cases and benchmarks, we carry out sensitivity tests, which can even serve to replan the work of the decision-makers.